PENERAPAN MANAJEMEN INFORMASI BERBASIS GEOSPATIAL WEB UNTUK ASET TANAH DAN BANGUNAN MILIK PEMERINTAH KABUPATEN PONTIANAK - , Albert Launardus, I Wayan Nuka Lantara, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to create a geospatial information management visualization for land and building assets database of the Pontianak Regency Government, making the three-dimensional view model of building assets and store asset information data processing by utilizing cloud computing technology for then overlaying this information into a global view of the whole earth surface. Processing and data analysis was performed by using a collaboration from some applications of Geographic Information Systems (GIS) to process spatial data, attribute data editing, making three-dimensional models of building visualization, storing and displaying this information data assets into three display mode: desktop, website and mobile. The results of asset database by utilizing the integration of geospatial information technology into the asset management concept through cloud computing service architecture is able to produce assets information with more communicative, able to improve data processing scalability and accessibility as well as supporting cost efficiency implementation of asset management. Developing this concept outside the scope of the asset management area can also be applied to many areas of public information such as land information, demographic information, taxpayer data information, or zoning and development areas information.